The Minimal Dominant Set is a Non-Empty Core-Extension - László Á. Kóczy; Luc Lauwers (Fondazione Eni Enrico Mattei (FEEM), 2003)
A set of outcomes for a TU-game in characteristic function form is dominant if it is, with respect to an outsider-independent dominance relation, accessible (or admissible) and closed. This outsider-independent dominance relation is restrictive in the sense that a deviating coalition cannot determine the payoffs of those coalitions that are not involved in the deviation. The minimal (for inclusion) dominant set is non-empty and for a game with a non-empty coalition structure core, the minimal dominant set returns this core.
Keywords: C71; 330; Core; Non-emptiness; Indirect dominance; Outsider-independence; Spieltheorie; Core; Theorie